(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Morphological andbioecological featuresof Oriental persimmon (Diospyros lotusL.)in the Forest-Steppe zone of Ukraine are elucidated. Reproductive ability, morphological and metrical characteristics of vegetative and generative organs are studied. The methods and terms of propagation are described.